Preliminary Study on Antioxidant and Antibacterial Activity of Kaffir Lime (Citrus hystrix DC) Leaf Essential Oil (Applied Research in Science and Technology, 2021)
This preliminary study aimed to examine the antioxidant and antibacterial activity of kaffir lime leaf essential oils (KLLEOs) in response to different growing locations and post-harvest handling. This study tested 9 samples, i.e., 8 KLLEOs with variation in growth location and post-harvest handling, and 1 standard citronellal solution. Thin layer chromatography was used to test the antioxidant and antibacterial activity of samples. Eluent in a mixture of hexane: ethyl acetate (5: 1) was chosen because it could provide a clear separation effect under visible light and after being sprayed with vanillin sulfate. KLLEOs originated from brown and green leaf powder had a stronger antioxidant activity than other samples. The sensitivity of KLLEOs to E. coli was lower than S. aereus, as indicated by fewer stains observed in E. coli glass plates rather than S. aereus ones. Standard citronellal compound at a concentration of 5 l ml-1 showed no antioxidant activity and at a concentration of 10 l ml-1 showed no antibacterial activity against both E. coli and S. aereus.